Effectiveness of Mobile based Agro-Advisory Services in Addressing Information Need of the Stakeholders: A Case of m KRISHI® - Madan Singh , R. Roy Burman , J. P. Sharma , V. Sangeetha and Mir Asif Iquebal, (Indian Journal of Extension Education, 2015)
Many information and communication technology (ICT) projects in Indian agriculture have emerged, either substitutingor supporting extension services by providing access to agricultural information to the farmers, but its access to thefarmers in remote villages is restricted due to the lack of infrastructure. It creates information asymmetry among farmers.Telecommunication, especially mobile phones have the potential to provide solution to the existing informationasymmetry in various lagging sectors like agriculture. mKRISHI® is one such project which made significantcontribution in information dissemination in some parts of India. The present study was undertaken for assessing itseffectiveness in information dissemination to the farmers in two districts of Maharashtra and Tamil Nadu wheremKRISHI® was working for the last six years. Data were collected from 60 respondents from the mKRISHI® memberfarmers. The effectiveness was measured by effectiveness index developed for the purpose. The study revealed that theextension services rendered by mKRISHI® were found to be highly effective by majority of the farmers (46.66 %).